"Click" Dendrimer‐Stabilized Palladium Nanoparticles as a Green Catalyst Down to Parts per Million for Efficient CC Cross‐Coupling Reactions and Reduction of 4‐Nitrophenol. Issue 11 (20th June 2014) - Deraedt, Christophe; Salmon, Lionel; Astruc, Didier
Abstract The concept of the nanoreactor valuably contributes to catalytic applications of supramolecular chemistry. Therewith molecular engineering may lead to organic transformations that minimize the amount of metal catalyst to reach the efficiency of enzymatic catalysis. The design of the dendritic nanoreactor proposed here involves hydrophilic triethylene glycol (TEG) termini for solubilization in water and water/ethanol mixed solvents combined with a hydrophobic dendritic interior containing 1, 2, 3‐triazole ligands that provide smooth stabilization of very small (1 to 2 nm) palladium nanoparticles (PdNPs). The PdNPs stabilized in such nanoreactors are extraordinarily active in water/ethanol (1/1) for the catalysis of various carbon‐carbon coupling reactions (Suzuki–Miyaura, Heck and Sonogashira) of aryl halides down to sub‐ppm levels for the Suzuki–Miyaura coupling of aryl iodides and aryl bromides. The reduction of 4‐nitrophenol to 4‐aminophenol in water also gives very impressive results. The difference of reactivity between the two distinct dendrimers with, respectively, 27 (G0) and 81 (G1) TEG termini is assigned to the difference of PdNP core size, the smaller G0 PdNP core being more reactive than the G1 PdNP core (1.4 vs. 2.7 nm), which is also in agreement with the leaching mechanism. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>